Chemical short-range order strengthening mechanism in CoCrNi medium-entropy alloy under nanoindentation. (1st March 2022) - Yang, Xiaofeng; Xi, Yongzhi; He, Chenyun; Chen, Hao; Zhang, Xiancheng; Tu, ShanTung
Graphical abstract: Abstract: The strengthening effect of chemical short-range order (SRO) structure in CoCrNi medium-entropy alloy (MEA) was investigated using molecular dynamics (MD) simulations of nanoindentation. The quantitative correlation between SRO parameters and mechanical properties was established. Results show that the strength and hardness of CoCrNi MEA increase with increasing chemical SRO parameters and reach a stable value with steady SRO structure. Compared with random solid solution (RSS) state model, the average hardness increases 8.1 % in an intermediate SRO model and 13.7 % in a stable SRO model. The dislocation nucleation force of SRO model is 55 % larger than RSS model. Moreover, dislocation pinning induced by local Ni SRO structure, as well as the promoted unique dislocation interaction were observed during the nanoindentation process. Finally, results also show that as the temperature rises, the enhancement of hardness becomes more significant ( 11.4 % at 70 K, 17.24 % at 300 K, and 23.8 % at 800 K ).